2018
DOI: 10.5267/j.msl.2018.2.004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of packaging elements on purchase intention: case study of Algerian customers

Abstract: The aim of this article is to study the impact of marketing innovation and the visual and verbal elements of packaging on customers purchase intentions. After a brief literature review, an empirical study is conducted among 140 customers of Coca-Cola brand in Tlemcen city. To this end, a model of intention has been developed to be tested by structural equations modeling. The results of this study showed that marketing innovation and the visual and verbal elements of packaging directly affect the purchase inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
0
5
0
3
Order By: Relevance
“…Овај аспект производа посебно је важан за оне производе који ће дуги низ година остати у дому потрошача (Creusen -Schoormans 2005). Група истраживача је у једнојстудији потврдила да вербални и визуелни елементи амбалаже производа позитивно утичу на намере потрошача при куповини (Benachenhoui dr. 2018).…”
Section: сензорни маркетингunclassified
“…Овај аспект производа посебно је важан за оне производе који ће дуги низ година остати у дому потрошача (Creusen -Schoormans 2005). Група истраживача је у једнојстудији потврдила да вербални и визуелни елементи амбалаже производа позитивно утичу на намере потрошача при куповини (Benachenhoui dr. 2018).…”
Section: сензорни маркетингunclassified
“…Selain itu, usahawan mikro juga sedar bahawa inovasi pembungkusan dapat meningkatkan prestasi perniagaan dan meningkatkan daya saing pasaran terutamanya apabila berhadapan dengan pesaing. Tingkah laku pembelian pengguna dipengaruhi oleh penampilan pembungkusan yang dapat membezakannya dengan produk pesaing (Benachenhou et al 2018). Justeru itu, penampilan pembungkusan yang baharu, maka, strategi pemasaran juga adalah perlu berbeza dan disesuaikan dengan keadaan semasa.…”
Section: Kesedaranunclassified
“…Walau bagaimanapun, usahawan mikro perlu meningkatkan tahap kesedaran akan kepentingan inovasi pembungkusan dari sudut pengguna. Hal ini kerana banyak kajian lepas telah membuktikan bahawa inovasi pembungkusan berupaya menarik tingkah laku pembelian dan berupaya menggamit emosi dalam kalangan pengguna (Benachenhou et al 2018;Bilovodska et al 2016;Imiru 2017). Oleh itu, agensi pembimbing perlu tingkatkan lebih banyak program berkaitan inovasi pembungkusan dengan www.msocialsciences.com pendekatan yang lebih kreatif agar usahawan mikro mempunyai kesedaran yang lebih mengenai kepentingan inovasi pembungkusan dalam pemasaran.…”
Section: Kesedaranunclassified
“…The study implemented factor analysis to determine important factors based on a questionnaire distributed among some employees of Pegah dairy producer and determined five factors including infrastructure, awareness, design and communication as important factors influencing consumers. Benachenhou et al (2018) investigated on the effect of marketing innovation and the visual and verbal elements of packaging on customers purchase intentions. They demonstrated that marketing innovation and the visual and verbal elements of packaging influenced on the purchase intentions of the customers of this brand.…”
Section: Introductionmentioning
confidence: 99%